ANALYSIS OF THE UTILIZATION OF SHOPEEFOOD FEATURES ON THE REVENUE OF MICRO, SMALL, AND MEDIUM-SIZED CULINARY BUSINESSES IN SOUTH JAKARTA - Warni, Auliya Rahma (Transpublika Publisher, 2023)
Shopee is an online Marketplace application for buying and selling on mobile phones easily and quickly. Shopee has a food delivery service called Shopee Food which has the same function and purpose as other food delivery services. This study aims to explore the benefits of the ShopeeFood feature on the income of micro, small and medium enterprises in the culinary field in South Jakarta. The place of this research was conducted at the location of MSMEs in the culinary field in the South Jakarta area, DKI Jakarta, named Rena Foodies. This research will be conducted in July 2022. This research uses 3 types of informants, namely main informants, key informants, and additional informants. This research data was obtained from interviews, observations and documentation. This research was conducted by collecting data through interviews with three resource persons, namely MSMEs, ShopeeFood parties, and ShopeeFood users. The research was conducted. From the analysis of the data collected, three main studies were produced, namely the influence obtained by MSME entrepreneurs in the South Jakarta area in developing ShopeeFood features, the condition of the sales level of culinary MSMEs in the city of South Jakarta after joining ShopeeFood and the obstacles experienced by culinary MSMEs while joining the ShopeeFood program.